A Modified in vitro Clot Lysis Assay Predicts Outcomes in Non-traumatic Intracerebral Hemorrhage Stroke Patients—The IRONHEART Study - Orbán-Kálmándi, Rita; Árokszállási, Tamás; Fekete, István; Fekete, Klára; Héja, Máté; Tóth, Judit; Sarkady, Ferenc; Csiba, László; Bagoly, Zsuzsa (Frontiers in Neurology, 2021)
Background: Non-traumatic intracerebral hemorrhage (ICH) accounts for 10-15% of all strokes and results in a higher rate of mortality as compared to ischemic strokes. In the IRONHEART study, we aimed to find out whether a modified in vitro clot lysis assay method, that includes the effect of neutrophil extracellular traps (NETs) might predict ICH outcomes. Patients and methods: In this prospective, observational study, 89 consecutive non-traumatic ICH patients were enrolled. Exclusion criteria included aneurysm rupture, cancer, liver- or kidney failure or hemorrhagic diathesis. On admission, detailed clinical and laboratory investigations were performed. ICH volume was estimated based on CT performed on admission, day 14 and 90. A conventional in vitro clot lysis assay (CLA) and a modified CLA (mCLA) including cell-free-DNA and histones were performed from stored platelet-free plasma taken on admission. Clot formation and lysis in case of both assays were defined using the following variables calculated from the turbidimetric curves: maximum absorbance, time to maximum absorbance, clot lysis times (CLT) and area under the curve (CLA AUC). Long-term ICH outcomes were defined 90 days post-event by the modified Rankin Scale (mRS). All patients or relatives provided written informed consent. Results: Patients with more severe stroke (NIHSS>10) presented significantly shorter clot lysis times of the mCLA in the presence of DNA and histone as compared to patients with milder stroke (10%CLT: NIHSS 0-10: median 31.5 [IQR:21.0-40.0] min vs. NIHSS>10: 24 [18-31.0] min, p=0.032). Shorter clot lysis times of mCLA showed significant association with non-survival by day 14 and with unfavorable long-term outcomes (mRS 0-1: 36.0 [22.5.0-51.0] min; mRS 2-5: 23.5 [18.0-36.0] min and mRS 6: 22.5 [18.0-30.5] min, p=0.027). Estimated ICH volume showed significant negative correlation with mCLA parameters, including 10%CLT (r=-0.3050, p=0.009). ROC analysis proved good diagnostic performance of mCLA for predicting poor long-term outcomes (AUC: 0.73 [0.57-0.89]). In a Kaplan-Meier survival analysis, those patients who presented with an mCLA 10%CLT result of >38.5 min on admission showed significantly better survival as compared to those with shorter clot lysis results (p=0.010). Conclusion: Parameters of mCLA correlate with ICH bleeding volume and might be useful to predict ICH outcomes.